PERLINDUNGAN INVESTOR DALAM PENGHAPUSAN SAHAM PADA LAYANAN URUN DANA BERBASIS TEKNOLOGI INFORMASI - Febrian Duta Adhiyaksa; Sharda Abrianti (Faculty of Law, Universitas Trisakti, 2023)
Currently, Financial Technology is very developed, one of the forms of Financial Technology that exists is Equity Crowdfunding, which is a new option for investing. The term Equity Crowdfunding has now changed to Securities Crowdfunding (SCF). In SCF, listed shares can also be delisted. The formulation of the problem in this paper is how investor protection by the issuer of the delisting of PT Mitra Kelola Abadi shares in the implementation of Information Technology-Based Crowdfunding services. The analysis in this research uses qualitative research with a normative approach, collecting data sourced from secondary data consisting of primary and secondary legal materials and concluded by deductive method. The results of the conclusion that has been conducted reveal deficiencies in the aspects of legal protection for investors related to the risk of delisting shares. There are violations identified in the share buyback process, where the violation violates the provisions in Article 38 of the Limited Liability Company Law, because it does not involve decisions obtained from the General Meeting of Shareholders. It is expected that there will be specific regulations governing the delisting process in the SCF.